(untitled) - Elvström, Paul (Boston, 2004)
Paul Elvstrom Explains the Racing Rules of Sailing has accompanied sailors to regattas since 1965. This new edition of the book--known to all simply as "Elvstrom" and famous for its plastic boats and wind arrows--incorporates the complete text of the International Sailing Federation's (ISAF) 2004 rules changes. It features color-coded explanations and interpretations of the rules with the help of two-color bird's-eyeview drawings. It also offers a full-color chart of race signals, a graphic quick-reference locator for the rules, a summary of recent rules changes, and procedural notes for filing a protest.
Keywords: Sailboat racing,Đua thuyền buồm; Rules,Nguyên tắc